Ni-Ti Shape Memory Alloy Coatings for Structural Applications: Optimization of HVOF Spraying Parameters. (28th June 2018) - De Crescenzo, Carmen; Karatza, Despina; Musmarra, Dino; Chianese, Simeone; Baxevanis, Theocharis; Dalla, Panagiota T.; Exarchos, Dimitrios A.; Dassios, Konstantinos G.; Matikas, Theodore E.
Abstract : This work aims at contributing to the development of a revolutionary technology based on shape memory alloy (SMA) coatings deposited on-site to large-scale metallic structural elements, which operate in extreme environmental conditions, such as steel bridges and buildings. The proposed technology will contribute to improve the integrity of metallic civil structures, to alter and control their mechanical properties by external stimuli, to contribute to the stiffness and rigidity of an elastic metallic structure, to safely withstand the expected loading conditions, and to provide corrosion protection. To prove the feasibility of the concept, investigations were carried out by depositing commercial NiTinol Ni50.8Ti (at.%) powder, onto stainless steel substrates by using high-velocity oxygen-fuel thermal spray technology. While the NiTinol has been known since decades, this intermetallic alloy, as well as no other alloy, was ever used as the SMA-coating material. Due to the influence of dynamics of spraying and the impact energy of the powder particles on the properties of thermally sprayed coatings, the effects of the main spray parameters, namely, spray distance, fuel-to-oxygen feed rate ratio, and coating thickness, on the quality and properties of the coating, in terms of hardness, adhesion, roughness, and microstructure, were investigated.